Stenotrophomonas maltophilia: The Landscape in Critically Ill Patients and Optimising Management Approaches - Nieves Carbonell; María Rosa Oltra; María Ángeles Clari (MDPI AG, 2024)
The aim of this review is to synthesise the key aspects of the epidemiology, current microbiological diagnostic challenges, antibiotic resistance rates, optimal antimicrobial management, and most effective prevention strategies for Stenotrophomonas maltophilia (SM) in the intensive care unit (ICU) population. In recent years, resistance surveillance data indicate that SM accounts for less than 3% of all healthcare-associated infection strains, a percentage that doubles in the case of ventilator-associated pneumonia (VAP). Interestingly, SM ranks as the third most isolated non-glucose fermenter Gram-negative bacilli (NFGNB). Although this NFGNB genus has usually been considered a bystander and colonising strain, recently published data warn about its potential role as a causative pathogen of severe infections, particularly pneumonia and bloodstream infections (BSI), not only for the classical immunocompromised susceptible host patients but also for critically ill ones even without overt immunosuppression. Indeed, it has been associated with crude 28-day mortality as high as 54.8%, despite initial response following targeted therapy. Additionally, alongside its intrinsic resistance to a wide range of common antimicrobials, various worldwide and local surveillance studies raise concerns about an increase in ICU settings regarding resistance to first-line drugs such as cotrimoxazole or tigecycline. This scenario alerts ICU physicians to the need to reconsider the best stewardship approach when SM is isolated in obtained samples from critically ill patients. Despite the coverage of this multidrug-resistant bacterium (MDRB) provided by some traditional and a non-negligible number of current pipeline antimicrobials, an ecological and cost-effective strategy is needed in the present era.